A Converse of Minkowski's Type Inequalities. (24th October 2010) - Meštrović, Romeo; Kalaj, David
Abstract : We formulate and prove a converse for a generalization of the classical Minkowski's inequality. The case when0 < p < 1 is also considered. Applying the same technique, we obtain an analog converse theorem for integral Minkowski's type inequality.